Antibiofilm activity and NMR-based metabolomic characterization of cell-free supernatant of Limosilactobacillus reuteri DSM 17938 - Vitale, Irene; Spano, Mattia; Puca, Valentina; Carradori, Simone; Cesa, Stefania; Marinacci, Beatrice; Sisto, Francesca; Roos, Stefan; Grompone, Gianfranco; Grande, Rossella (Frontiers in Microbiology, 2023)
The microbial biofilm has been defined as a “key virulence factor” for a multitude of micro-organisms associated with chronic infections. Its multifactorial nature and variability as well as an increase in antimicrobial resistance suggest the need to identify new compounds, alternative to the commonly used antimicrobials. The aim of this study was to assess the antibiofilm activity of Cell Free Supernatant (CFS) and its sub-fractions (SurE 10K with molecular weight less than 10 kD and SurE with molecular weight less than 30 kD), produced by Limosilactobacillus reuteri DSM 17938, versus biofilm-producing bacterial species. The Minimum Inhibitory Biofilm Concentration (MBIC) and the Minimum Biofilm Eradication Concentration (MBEC) were determined via the evaluation of viability by using three different methods. The CFS showed a promising antibiofilm activity against the biofilm developed by clinically relevant microorganisms. We performed an NMR metabolomic analysis of CFS and SurE 10K allowing us to identify and quantify several compounds, mainly organic acids and amino acids with lactate, being the most abundant metabolite in all the analyzed samples. The CFS and SurE 10K were characterized by a similar qualitative profile, with the exception of formate and glycine detected only in CFS. Finally, storage stability of these postbiotics was evaluated by a colorimetric assay by analyzing changes in the CIEL*a*b parameters, assessing the better conditions to analyze and use these matrices for correct preservation of bioactive compounds.